1978
DOI: 10.2343/geochemj.12.153
|View full text |Cite
|
Sign up to set email alerts
|

The secondary iron oxidehydroxide mineralogy of some deep-sea and fossil manganese nodules: A Moessbauer and X-ray study.

Abstract: Mossbauer spectroscopy utilizing precise computer-based curve fitting procedures and X-ray diffrac tion methods have been used to study four deep-sea and one fossil marine manganese nodule. They have shown that X-ray amorphous goethite (a-FeOOH) and probably akaganeite (P-FeOOH) are the secondary iron oxidehydroxide phases present in the deep-sea nodules. The fossil nodule contained goethite with a larger particle size (approx. 350A) which had presumably been formed by the recrystallization of X-ray amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…This view is supported .by the recent work of JOHNSTON and GLASBY (1978) using Mossbauer spectroscopy which has shown that recrystallisation of the iron oxide phase of the Timor nodule has taken place since the nodule was exposed and this may have led to some element redistribution. In spite of this, the trace element composition can be recognised as being typical of that of a deep-sea nodule.…”
Section: Elderfield 1976)supporting
confidence: 67%
See 1 more Smart Citation
“…This view is supported .by the recent work of JOHNSTON and GLASBY (1978) using Mossbauer spectroscopy which has shown that recrystallisation of the iron oxide phase of the Timor nodule has taken place since the nodule was exposed and this may have led to some element redistribution. In spite of this, the trace element composition can be recognised as being typical of that of a deep-sea nodule.…”
Section: Elderfield 1976)supporting
confidence: 67%
“…Summaries of sample locations, sample descritpions, associated sediment types, nodule mineralogy and previous element ana lyses have been given by JOHNSTON and GLASBY (1978 , Table 1). An account of the iron oxide mineralogy of the nodules has also been pres ented by JOHNSTON and GLASBY (1978).…”
Section: Sample Location and Descriptionmentioning
confidence: 99%
“…99 South of the Marquesas Fracture Zone in Area G) and that these spectra are identical to those obtained by JOHNSTON and GLASBY (1978) for a limited number of deep-sea nodules from the Southwestern Pacific Basin, from north of the Indian-Antarctic Ridge and from the Carlsberg Ridge, Indian Ocean. Since these nodules were chosen specifically to re present different environments of deposition (particularly in respect to the biological produc tivity of the overlying surface seawater), the data offer persuasive evidence that the iron min eralogy of all deep-sea manganese nodules is identical irrespective of location.…”
Section: Mossbauer Spectroscopysupporting
confidence: 54%
“…On the basis of the Mossbauer spectra and parameters now available, it is very difficult to distinguish fi and y-FeOOH phases. The agree ments of JOHNSTON and GLASBY (1978) and regarding the stabilisation of a-FeOOH by chloride ions in seawater, however, may still make this the preferred iron oxide hydroxide mineral in marine manganese nodules. Deep-sea nodules may therefore still consist of a mixture of a and O-FeOOH.…”
Section: Mossbauer Spectroscopymentioning
confidence: 99%
“…Logan et al (1976) suggested on the basis of M6ssbauer data that akagan6ite is present in some New Zealand soils. Johnston (1977) identified akagan6ite coating andesite boulders at White Island volcano, New Zealand. Johnston and Glasby (1978) reported akagan6ite as a secondary oxyhydroxide mineral in marine and fossil manganese nodules.…”
mentioning
confidence: 99%